Comparison of clinical outcome of small-incision lenticule intrastromal keratoplasty and FS-LASIK for correction of moderate and high hyperopia - Li Zhang; Yue-Hua Zhou; Chang-Bin Zhai; Jing Zhang; Yan Zheng (International Journal of Ophthalmology, 2022)
AIM: To compare the clinical outcome of small-incision lenticule intrastromal keratoplasty (sLIKE) and femtosecond laser-assisted in situ keratomileusis (FS-LASIK) for correction of moderate and high hyperopia. METHODS: A case-controlled clinical study was performed. Twenty right eyes of 20 moderate and high hyperopia patients underwent sLIKE (sLIKE group) and 22 right eyes of 22 moderate and high hyperopia patients underwent FS-LASIK (FS-LASIK group) were enrolled in this study from October 2015 to October 2017. Visual acuity, refractive error, corneal thickness, and keratometry were compared between the groups before and 1y postoperatively. RESULTS: The postoperative uncorrected near visual acuity (UNVA) and uncorrected distance visual acuity (UDVA) were improved in the two groups. The UNVA reached J1 in 15 eyes (75.0%) in the sLIKE group and 5 eyes (22.7%) in the FS-LASIK group 1y after surgery (χ2=11.476, P=0.001). The UDVA was equal or better than the preoperative CDVA in 16 eyes (80.0%) in the sLIKE group and 8 eyes (36.4%) in the FS-LASIK group, respectively (X2=8.145, P=0.004). No eyes lost any line of best-corrected visual acuity (BCVA) in either group. The amount of postoperative residual hyperopia in the sLIKE group was significantly less than in the FS-LASIK group (Z=-2.841, P=0.004). The postoperative keratometry and corneal thickness were significantly higher in the sLIKE group than in the FS-LASIK group (t=4.411, 10.279, P<0.001). The SRI and SAI of the sLIKE group were significantly higher than that in the FS-LASIK group. There was no statistically significant difference in mean decentration between the two groups. CONCLUSION: sLIKE has better visual and refractive outcome than FS-LASIK for correction of moderate and high hyperopia.